2021
DOI: 10.2147/ijwh.s327753
|View full text |Cite
|
Sign up to set email alerts
|

Labor Companionship in Labor and Delivery at Debremarkos Town Public Health Facilities: Magnitude and Associated Factors

Abstract: Background Labor companionship is a human interactive process that provides social support during the childbirth process. Despite it being one component of respectful maternity care (RMC) that is used for quality assurance to achieve the sustainable goal of maternal and neonatal mortality reduction, there is limited evidence about the current status of birth companionship. The study was aimed to assess labor companion and its associated factors at Debremarkos town public health facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In fact, not all hospitals allow the presence of companions, in Thailand, where family members usually were not allowed to be present during intrapartum [ 22 ]. Others like Ethiopia have a low labour companionship, which was found to be 14.6% [ 23 ]. In a recent study in Burkina Faso, where 77 women, companions, and health workers were interviewed about their beliefs, opinions, and policies about labour companions, they found that hospitals were not allowing companions during labour and birth [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, not all hospitals allow the presence of companions, in Thailand, where family members usually were not allowed to be present during intrapartum [ 22 ]. Others like Ethiopia have a low labour companionship, which was found to be 14.6% [ 23 ]. In a recent study in Burkina Faso, where 77 women, companions, and health workers were interviewed about their beliefs, opinions, and policies about labour companions, they found that hospitals were not allowing companions during labour and birth [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a chosen birth support companion also resulted in an increase in labouring women's self-efficacy. In conclusion, a negative birth experience is frequently caused by the lack of a labour partner (Asratie et al, 2021). The function of the birth companion includes all non-clinical elements of care.…”
Section: Introductionmentioning
confidence: 96%
“…Despite all the aforementioned clarities about birth companionship which can be achieved whenever their desire is respected, there is limited evidence that shows the status of women's desires about birth companionship. The different studies have been done about the status of birth companions among postpartum period ( 12 , 30 ), rather the desire of pregnant women about birth companionship was not yet studied in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%